2017
DOI: 10.3390/su9050856
|View full text |Cite
|
Sign up to set email alerts
|

Food Image Recognition via Superpixel Based Low-Level and Mid-Level Distance Coding for Smart Home Applications

Abstract: Abstract:Food image recognition is a key enabler for many smart home applications such as smart kitchen and smart personal nutrition log. In order to improve living experience and life quality, smart home systems collect valuable insights of users' preferences, nutrition intake and health conditions via accurate and robust food image recognition. In addition, efficiency is also a major concern since many smart home applications are deployed on mobile devices where high-end GPUs are not available. In this paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
(86 reference statements)
0
13
0
Order By: Relevance
“…Novel food recognition systems for dietary evaluation have been enabled by the increasing use of smartphones and the advancement of artificial intelligence and computer vision technologies. Various studies have already been conducted in this domain (Zheng et al, 2017;He et al, 2015;Ravì et al, 2015;Nayak et al, 2020;Chopra & Purwar, 2021). The first thing users need to do in food consumption tracking and recommendation apps is track their food consumption.…”
Section: Functionalitymentioning
confidence: 99%
“…Novel food recognition systems for dietary evaluation have been enabled by the increasing use of smartphones and the advancement of artificial intelligence and computer vision technologies. Various studies have already been conducted in this domain (Zheng et al, 2017;He et al, 2015;Ravì et al, 2015;Nayak et al, 2020;Chopra & Purwar, 2021). The first thing users need to do in food consumption tracking and recommendation apps is track their food consumption.…”
Section: Functionalitymentioning
confidence: 99%
“…Admittedly, her sister has suggested that erythritol is a popular sugar substitute in recent times. However, two doubts remained to be resolved: (1) will erythritol not lose its sweetness during baking, (2) in what ratio to replace sugar with erythritol to get a similar sweetness?…”
Section: Aspects Of a Dishmentioning
confidence: 99%
“…The computational support for handling tasks, such as recommending ingredient substitutes, falls into a relatively new area of food computing [1]with a broad spectrum of applications, such as food recognition [2], detecting food intake with the use of sensors [3], and computational diet management [4]. Many recent approaches in food computing and diet management use artificial intelligence (AI), both statistical methods (based on various forms of machine learning) and symbolic ones (based, for instance, on the usage of knowledge graphs [5]).…”
Section: Introductionmentioning
confidence: 99%
“…However, the performance is poor due to the low complexity of the methods. The mid-level methods, with much higher complexity and better performance, result in around 1-2 s/ image of speed on CPU implementation (0.8 s/image on 8 core CPU for RFDC [9] and 1.5 s/image on a single CPU for SFP [10]). On the other hand, benefiting from recently developed graphics processing unit (GPU) computing hardwares, deep learning methods achieved high speed on GPU despite the large complexity of deep learning models.…”
Section: Selection Of Number Of Clusters Kmentioning
confidence: 99%
“…Bossard et al [9] proposed a random forest‐based method to mine FPs with high probability for each class. Zheng et al [10] introduced a density ratio‐based approach to mine FPs with more appearances in target class and less appearances in background classes. Since these models employ low‐level local features with IFV encoding to represent mid‐level FPs, their recognition power is limited.…”
Section: Related Workmentioning
confidence: 99%